PET particles raise microbiological concerns for human health while tyre wear microplastic particles potentially affect ecosystem services in waters - Sathicq, María Belén (2022)
Although abundant and chemically peculiar, tyre wear microplastic particles (TWP) and their impact on the microbial communities in water are largely understudied. We tested in laboratory based semi-continuous cultures the impact of TWP and of polyethylene terephthalate (PET) derived particles (following a gradient of relative abundance) on the pathobiome (the group of potential human pathogenic bacteria) of a freshwater microbial community exposed to contamination by the effluent of a urban wastewater treatment plant, for a period of 28 days. We could define the modulated impact of the two types of microplastic particles: while PET does not favour bacterial growth, it offers a refuge to several potential pathogens of allochthonous origin (from the treated sewage effluent), TWP act as an additional carbon source, promoting the development and the massive growth of a biofilm composed by fast-growing bacterial genera including species potentially harmful and competitive in abating biodiversity in surface waters. Our results demonstrate the different ecological role and impact on freshwater environments of TWP and PET particles, and the need to approach the study of this pollutant not as a whole, but considering the origin and the chemical composition of the different particles.